The Marker of Sexuality in Nedjma’s the Almond: A Semiotic Approach - Nur, Riola Haya; Ahmad, Ardiansyah; Nurfadhilah, Auliyanti Sahril; Atpas, Andi Anggun (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
Sexuality is the interesting issue to talk about as it is always connected to social and cultural value, especially for women as said women’s bodies are cultural sites. This study is concerned to the sexuality markers used in the novel by Nedjma, The Almond. The study shows how markers have some connotative meanings based on the cultural context and religion context. This study applies semiotic approach from Umberto Eco in interpreting the sexuality markers in the novel. The method used in this study is qualitative data analysis to the collected data obtained from “The Almond” novel and the secondary data from other books, journals, dictionaries and articles (e-text) from the internet. It is found some meaning connected to the myth of Maroccan, Greek, and Egyptians cultures, also to Christian and Buddhism. This study will have significant contribution to understand how symbols or markers have different meaning in different cultures.